Development and validation of a simple and sensitive size-exclusion chromatography method for quantitative determination of heparin in pharmaceuticals - Matanović Maja Radivojša; Grabnarm Iztok; Grabnar Pegi Ahlin; Roškar Robert (Acta Pharmaceutica)
Heparin is widely used as an anticoagulant for the treatment and prevention of various thrombotic diseases. However, due to its high anionic charge, heterogeneity in size distribution and high polarity, its analysis is very challenging. In this paper, a novel method based on size-exclusion chromatography (SEC) for quantitative determination of intact heparin in pharmaceuticals is presented. Analyses were performed on a BioSep-SEC-S 2000 column with Larginine solution at pH 6.5 as mobile phase and UV detection at 210 nm. The proposed method was found to be selective, linear (R2 > 0.997) over the concentration range of 3.1 to 1222 μg mL-1, with a limit of detection of 1.0 μg mL-1. Intraday and inter-day precision were below 5.1 % and inaccuracy expressed as bias did not exceed 6.5 %. The reported method is simple, selective, sensitive, and requires no laborious sample preparation, which makes it appropriate for routine quantitative analysis of heparin in pharmaceuticals